2021
DOI: 10.1039/d1dt02085d
|View full text |Cite
|
Sign up to set email alerts
|

Antimony diiminopyridine complexes

Abstract: The stoichiometric reactions of antimony trichloride, trimethylsilyl trifluoromethanesulfonate, and diiminopyridine ligands lead to the formation of N,N′,N″-chelated SbCl2 cationic complexes. Methyl, phenyl substituents on the imine carbons of the ligand...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 58 publications
0
15
1
Order By: Relevance
“…Diiminopyridine (DIMPY) ligands offer a rigid pincer framework capable of stabilizing reactive metal centers competent in activating bonds that have been applied in the catalytic polymerization of olefins as well as promoting cycloaddition and borylation reactions . Almost all of the heavy group 13–16 elements have been reported, but for row 6, complexes exist only for Tl and Pb . The cationic lead complex ( C ) bears an isothiocyanate ligand with an unusual geometry at lead as the ligand retains planarity with the isothiocyanate perpendicular to the PbN 3 plane rationalized by the Pb­(II) center having a stereochemically active lone pair .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diiminopyridine (DIMPY) ligands offer a rigid pincer framework capable of stabilizing reactive metal centers competent in activating bonds that have been applied in the catalytic polymerization of olefins as well as promoting cycloaddition and borylation reactions . Almost all of the heavy group 13–16 elements have been reported, but for row 6, complexes exist only for Tl and Pb . The cationic lead complex ( C ) bears an isothiocyanate ligand with an unusual geometry at lead as the ligand retains planarity with the isothiocyanate perpendicular to the PbN 3 plane rationalized by the Pb­(II) center having a stereochemically active lone pair .…”
Section: Introductionmentioning
confidence: 99%
“…The cationic lead complex ( C ) bears an isothiocyanate ligand with an unusual geometry at lead as the ligand retains planarity with the isothiocyanate perpendicular to the PbN 3 plane rationalized by the Pb­(II) center having a stereochemically active lone pair . The thallium­(I) complex ( D ) could be crystallized as a dimer through Tl-arene interactions with the ligand of another molecule or could be co-crystallized with benzene or toluene to form Tl-η arene complexes, with the arene bridging two thallium centers . Thallium complex D has notably long Tl–N bonds that are classified as weak interactions and the ligand binds lead more tightly in C [Tl–N range = 2.739(2)–2.795(2) c.f.…”
Section: Introductionmentioning
confidence: 99%
“…1F). 19 Based on these recent results, it is obvious that the pincer chemistry of heavy Group 15 elements constitutes an exciting and quickly developing area.…”
Section: Introductionmentioning
confidence: 99%
“…[16] The tripodal tetradentate ligands such as tris(benzoimidazol)amine [17] or tris(2-pyridyl)phosphine and analogues [18] also efficiently coordinate to these positively charged pnictogen acceptors (B and C respectively). Very recently, Martin et al have reported the Sb(III) [19] and Bi(III) [20] cationic complexes introducing the redox-active diiminopyridine as ligand (D). The authors were capable of isolating both [BiCl 2 ] + and [BiCl] 2 + species, while reported only [SbCl 2 ] + in the case of antimony.…”
Section: Introductionmentioning
confidence: 99%
“…The authors were capable of isolating both [BiCl 2 ] + and [BiCl] 2 + species, while reported only [SbCl 2 ] + in the case of antimony. [19,20] The substitution on the α-carbon plays crucial role in terms of the product isolation, with the methyl substitution leading to complex mixture formations. [21] Generally, the Schiff base ligands are unpopular for the stabilization of heavier pnictogen cationic species due to their competing redox behavior impeding simple coordination abilities.…”
Section: Introductionmentioning
confidence: 99%